2021
DOI: 10.26773/mjssm.210304
|View full text |Cite
|
Sign up to set email alerts
|

Peak External Intensity Decreases across Quarters during Basketball Games

Abstract: The purpose of this study was to compare peak external intensities across game quarters in basketball. Eight semi-professional male players were monitored using accelerometers. For all quarters, peak intensities were determined via moving averages for PlayerLoad/minute (PL·min-1) using sample durations of 15 s, 30 s, 1 min, 2 min, 3 min, 4 min, and 5 min. Linear mixed models and effect sizes (ES) were used to compare peak intensities between quarters for each sample duration. Small decreases in peak PL·min-1 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…Alternatively, the fact that players with more playing time before each PD episode achieved lower peak activity outputs may have been influenced by non-fatigue-related factors. For example, the PD accomplished by players may depend on the team lineup used when they are active in the game due to variations in player capacities (Alonso et al, 2020), team cohesion, and tactical approaches, as well as the stage of the game in which they are competing (e.g., game pace may decline during latter periods) (Fox, Salazar, et al, 2020; García et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the fact that players with more playing time before each PD episode achieved lower peak activity outputs may have been influenced by non-fatigue-related factors. For example, the PD accomplished by players may depend on the team lineup used when they are active in the game due to variations in player capacities (Alonso et al, 2020), team cohesion, and tactical approaches, as well as the stage of the game in which they are competing (e.g., game pace may decline during latter periods) (Fox, Salazar, et al, 2020; García et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…PDs were calculated for each variable in each quarter in each game for each player across 30-s, 45-s, 1-min, 2-min, and 5-min windows. These time windows were chosen given they have been identified as the most practical to consider in basketball (Alonso et al, 2020; Fox, Salazar, et al, 2020; Vázquez-Guerrero et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, analyzing external peak demands (PDs) may provide a different insight. The PD, defined as the most intense activity experienced by players for a selected variable across a specified timeframe of interest ( Alonso et al, 2020 ; Alonso Perez-Chao et al, 2021 ), has been quantified for basketball players using many external load variables (e.g., player load and distance) and time windows (e.g., 1 min and 2 min) ( Fox et al, 2020a ; Alonso et al, 2020 ; Fox et al, 2020b ; Vázquez-Guerrero et al, 2020 ; Vázquez-Guerrero and Garcia 2020 ; Alonso Perez-Chao et al, 2021 ). Additionally, moving average has been proved as the most accurate method to determine the peak intensities ( Cunningham et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning fluctuations, research findings carried out in basketball have revealed that average external physical demands decline across games, being higher during the first quarter than the last game quarter or overtime ( Scanlan et al, 2015 ; García et al, 2020 ). According to external PD, a previous study suggested that peak intensities decrease across quarters ( Fox et al, 2020b ). Similarly, the literature related to other sports such as soccer showed higher external PD during the first half compared to the second ( Oliva-Lozano et al, 2020 ; Bradley and Noakes 2013 ).…”
Section: Introductionmentioning
confidence: 99%